2020
DOI: 10.12669/pjms.36.4.1638
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of NMP 22 and urine cytology for detection of transitional cell carcinoma urinary bladder taking cystoscopy as gold standard

Abstract: Objective: To determine diagnostic accuracy of NMP 22 and urine cytology in the detection of transitional cell carcinoma (TCC) urinary bladder taking cystoscopy as a gold standard in patients having provisional diagnosis of bladder cancer (BC). Methods: This cross sectional validational study enrolled 380 patients fulfilling selection criteria and was conducted at Armed Forces Institute of Urology (AFIU) Rawalpindi, Pakistan form July 2018 to July 2019. The urine sample collected underwent NMP22 and cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…Results of the literature search 397 relevant literatures were retrieved, including 86 English literatures and 311 Chinese literatures. In strict accordance with the inclusion and exclusion criteria, 385 documents that did not meet the requirements such as duplicate documents, reviews, non-clinical research documents, and dissertations were removed, and 12 documents were finally included, [11][12][13][14][15][16][17][18][19][20][21][22] which included 2456 cases of study objects. All tests directly provide or can be calculated to obtain the complete data of the four-diagnosis table, and all evidence such as cystoscopy biopsy or postoperative pathological examination results is used as the gold standard.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of the literature search 397 relevant literatures were retrieved, including 86 English literatures and 311 Chinese literatures. In strict accordance with the inclusion and exclusion criteria, 385 documents that did not meet the requirements such as duplicate documents, reviews, non-clinical research documents, and dissertations were removed, and 12 documents were finally included, [11][12][13][14][15][16][17][18][19][20][21][22] which included 2456 cases of study objects. All tests directly provide or can be calculated to obtain the complete data of the four-diagnosis table, and all evidence such as cystoscopy biopsy or postoperative pathological examination results is used as the gold standard.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…However, some studies have shown that NMP22 had better specificity than sensitivity. For example, the results of both Rhijn, Bwgv et al, and MT Sajid et al, showed that the sensitivity of NMP22 was lower than the specificity, the reason may be related to the different selected thresholds between the studies and the differences in the number of patients 13,14 . In the SF Shariat study, NMP22 predicted bladder cancer with equal sensitivity and specificity at a threshold of 6.5 U/ml, and was preferable to the 10 U/ml cut‐point across all pathological stages and grades 15 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…NMP-22 is a quick, point of care test having higher sensitivity. In a diagnostic test that included 380 samples, the sensitivity of NMP-22 was 81.9% but at the cost of specificity of 76.97% ( 37 ). According to a meta-analysis that included 22 studies, the diagnostic accuracy of urine cytokeratin 20 for bladder cancer is improved with the progression of tumor stage and grade ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“… 3 At present, for patients without surgical contraindications, cystoscopy and transurethral resection of bladder tumor (TURBT) are still the gold standard for NMIBC treatment because of their minimal invasion, less pain and rapid postoperative recovery. 4 However, NMIBC still has a high risk of recurrence after surgery, and postoperative adjuvant intravesical chemotherapy is needed to eliminate residual tumor cells and reduce the recurrence rate. 5 Currently, there are many drugs used in intravesical chemotherapy, such as mitomycin, pirarubicin and epirubicin, which have no obvious advantage in preventing recurrence compared with another drug.…”
Section: Introductionmentioning
confidence: 99%